Impact of mental disorders on attendance at school. Issue 1 (April 2019) - Lawrence, David; Dawson, Vaille; Houghton, Stephen; Goodsell, Ben; Sawyer, Michael G
Mental disorders are among the most common and disabling conditions affecting children and adolescents. Patterns of school attendance among students with and without mental disorders were examined using data from the 2013–2014 Australian Child and Adolescent Survey of Mental Health and Wellbeing. One in seven school students had a mental disorder in the previous 12 months, with attention-deficit/hyperactivity disorder and anxiety being the most common. Students with a mental disorder had lower school attendance – being absent for 11.8 days per year in Years 1–6, 23.1 days per year in Years 7–10 and 25.8 days per year in Years 11–12, on average. In comparison, students without mental disorders were absent an average of 8.3 days (Years 1–6), 10.6 days (Years 7–10) and 12.0 days (Years 11–12) per year. Among students with a mental disorder, absences due to the disorder accounted for 13.4% of all days absent from school. This increased across years in school from 8.9% in Years 1–6 to 16.6% in Years 11–12. Improving prevention, early intervention, treatment and management of mental disorders may lead to significant improvements in school attendance.